The Effectiveness of Herbal Plant Extracts in Burn Wound Care: A Systematic Literature Review - NURLELA PETRA SARAGIH; Chrismis Novalinda Ginting; Tiarnida Nababan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Burns are tissue injuries caused by various thermal, chemical, or electrical agents, resulting in serious skin damage that requires comprehensive management. Traditional burn care often utilizes herbal plants due to their bioactive compounds, which have the potential to accelerate the healing process and reduce complications. Objective: This study aims to systematically examine the effectiveness of various medicinal plant extracts in accelerating the healing of Grade I and II burns, based on evidence from relevant experimental studies. Method: The research methodology follows the PRISMA guidelines, employing a literature review to identify experimental studies evaluating the efficacy of medicinal plant extracts in burn management published between 2019 and 2025 in both Indonesian and English. The search process utilized electronic databases such as Google Scholar and ResearchGate, using a combination of keywords including